Analysis Of The Impleimentation Of The Permendagri Regulation On Inner Village Financial Management Village Fund Allocation (Add) For Suka Village Prosperous District North Bengkulu - Ismawati, Desi; Fitriano, Yun; Gayatri, Ida Ayu Made Ermeytha (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The purpose of this study was to determine the implementation of the Permendagri on village financial management in the allocation of village funds in Suka Makmur Village. The method used in this research is a qualitative research method with a comparative approach. The data collection techniques used by the author are observation, interviews and documentation. The results showed that the analysis of the implementation of Permendagri Number 20 of 2018 concerning village financial management in the allocation of village funds in Suka Makmur Village was generally not in accordance, this can be seen from the stages in village financial management consisting of the planning stage, the implementation of which was not in accordance because the planning and implementation work time was not in accordance with Permendagri No. 20 of 2018. Meanwhile, the administration, reporting and accountability stages are largely said to be in accordance because they refer to Permendagri No. 20 of 2018. There are several things such as the lack of transparency to the community regarding the planning that will be carried out in Suka Makmur Village.